Opportunities and challenges for newborn screening and early diagnosis of rare diseases in Latin America - Giugliani, Roberto; Castillo Taucher, Silvia; Hafez, Sylvia; Oliveira, Joao Bosco; Rico-Restrepo, Mariana; Rozenfeld, Paula; Zarante, Ignacio; Gonzaga-Jauregui, Claudia (Frontiers in Genetics, 2022)
Rare diseases (RDs) cause considerable death and disability in Latin America. Still, there is no consensus on their definition across the region. Patients with RDs face a diagnostic odyssey to find a correct diagnosis, which may last many years and creates a burden for caregivers, healthcare systems, and society. These diagnostic delays have repercussions on the health and economic burden created by RDs and continue to represent an unmet medical need. This review analyzes barriers to the widespread adoption of newborn screening (NBS) programs and early diagnostic methods for RDs in Latin America and provides recommendations to achieve this critical objective. Increasing the adoption of NBS programs and promoting early diagnosis of RDs are the first steps to improving health outcomes for patients living with RDs. A coordinated, multistakeholder effort from leaders of patient organizations, government, industry, medical societies, academia, and healthcare services is required to increase the adoption of NBS programs. Patients’ best interests should remain the guiding principle for decisions regarding NBS implementation and early diagnosis for RDs.